2020
DOI: 10.1093/cid/ciaa579
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of Patients With Human Immunodeficiency Virus With COVID-19

Abstract: Little is known about the clinical outcomes of HIV patients infected with SARS-CoV-2. We describe 47 patients referred to our hospital between 21 February and 16 April 2020 with proven/probable COVID-19, 45 (96%) of whom fully recovered and two died.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
274
6
20

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(337 citation statements)
references
References 19 publications
37
274
6
20
Order By: Relevance
“…Regarding Casado et al [24] , the mean age is slightly lower in our cohort, with lower rates of comorbidities; also less patients had a history of severe immunodeficiency (<200 CD4) and time before infection by HIV was shorter (10.8 years vs. 19.5). Our data are even more similar to those described by Gervasoni et al [25] . Härter's cohort [26] has a similar mean age but showed higher severity, hospitalization, admission to ICU and mortality rates.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding Casado et al [24] , the mean age is slightly lower in our cohort, with lower rates of comorbidities; also less patients had a history of severe immunodeficiency (<200 CD4) and time before infection by HIV was shorter (10.8 years vs. 19.5). Our data are even more similar to those described by Gervasoni et al [25] . Härter's cohort [26] has a similar mean age but showed higher severity, hospitalization, admission to ICU and mortality rates.…”
Section: Discussionsupporting
confidence: 93%
“…In spite of a similar severe disease rate (28,6% vs. 25%), both hospital admission rate (32.3% vs. 55%) and patients who required ICU care (3.1 vs. 12%) were significantly lower than that of Casado's findings [24] ; however, a similar mortality rate was observed (3.17% vs. 4%). Our data are closer to Gervasoni et al [25] , with similar rates of hospital admission, severity, and ICU requirements.…”
Section: Discussionsupporting
confidence: 89%
“…There are rapidly growing information on COVID-19 infection, however, the data in HIV population remains contradictory [7,8]. Previous studies observed that low CD4 + T cell counts could actually protect against severe form of COVID-19, which suggested that immune system activation may actually increase the injury caused by COVID-19 and low CD4 + T cell counts might protect HIV-positive individuals from developing the cytokine storm observed in patients with COVID-19 [9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, we managed few cases of HIV/SARS-CoV-2 coinfections. Most of them were admitted with a moderate COVID-19 disease and had optimal outcomes, despite a higher average age and a higher proportion of patients with comorbidities (75%) in comparison with other cohorts (17,18).…”
Section: Discussionmentioning
confidence: 96%